Use of dapagliflozin in patients with advanced diabetic kidney disease - Hyun Sun Park; Youn Joo Jung; Dong-Young Lee; Kyoung Hyoub Moon; Beom Kim; Hae Won Kim (The Korean Society of Nephrology, 2018)
Sodium-glucose cotransporter-2 (SGLT2) inhibitors are effective for overweight diabetic patients through the induction of glucosuria. However, SGLT2 inhibitors are not recommended for patients with advanced chronic kidney disease (CKD) because they may aggravate renal function and thus become less effective in controlling blood glucose in this patient population. We suggest that adequate hydration would be helpful to prevent the side effects of SGLT2 inhibitors in diabetic patients with advanced CKD. In this study, we review five cases of SGLT2 inhibitor therapy, specifically with dapagliflozin, for the treatment of diabetes mellitus in patients with advanced CKD. The patients experienced dramatic weight reduction, improved glucose control, and further benefits without aggravation of renal function.